Enhancing Da'wah Quality Through ICT Innovations: A Case Study of Dayah Jamiah Al-Aziziyah - Muhibuddin Alamsyah; Yusfriadi Abda; Amiruddin (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to analyze the use of information and communication technology (ICT) in improving the quality of da'wah at Dayah Jamiah Al-Aziziyah, with a focus on the performance of the Head of Multimedia. Using a descriptive qualitative approach and case study method, data were collected through in-depth interviews, observations, and documentation. The analysis was carried out using the Miles and Huberman model. The results of the study indicate that the use of digital media such as social media, videos, and online platforms allows da'wah messages to reach a wider and more effective audience. The Head of Multimedia plays an important role in managing content and strategies for disseminating digital da'wah. This study emphasizes the importance of ICT mastery by da'i in strengthening the quality and reach of da'wah in the digital era.